The Relationship Between Social Support and Resilience in Adolescents at the Harapan Adolescent Orphanage - Lovi Setyowati, Era (International Journal of Social Science, Education, Communication and Economics, 2024)
The aim of this research is to examine the relationship between social support and resilience in adolescents in orphanages. This study uses a quantitative approach. Data collection in this research used a resilience measuring scale and a social support measuring scale in the form of a Likert scale. The respondents in this study were 100 teenagers from orphanages. The sampling method used in this research was purposive sampling with the criteria that the subjects taken were orphanage teenagers who had lived at least 1 year in the orphanage. The data obtained was analyzed using a correlation analysis technique of 0.404 (p=0.000), which means there is a very significant relationship between social support and resilience in teenagers in orphanages. This means that the higher the social support, the higher the resilience. Conversely, it means that the lower the social support, the lower the resilience.